New species and new records of sponge-inhabiting barnacles (Cirripedia, balanidae, acastinae) from Australia - Hosie, Andrew M.; Fromont, J.; Munyard, Kylie; Jones, D.S. (MDPI, 2021)
The subfamily Acastinae contains a diverse group of barnacles that are obligate symbionts of sponges and alcyonacean and antipatharian corals. Integrating morphological and genetic (COI) data to compare against known species, this paper reports on nine species of sponge-inhabiting barnacles of the subfamily Acastinae, including three undescribed species (Acasta caveata sp. nov., Euacasta acutaflava sp. nov., and E. excoriatrix sp. nov.) and three species previously not recorded in Australian waters (A. sandwichi, Pectinoacasta cancellorum, and P. sculpturata). The new species are distinguished from similar species by a suite of morphological characters as well as genetic distances. A lectotype for Pectinoacasta cancellorum is designated. Sponge hosts were identified for all specimens where possible and are represented by 19 species from eight families and five orders.